Costello syndrome in two Brazilian children. Issue 1 (January 1998) - Pratesi, R; Santos, M; Ferrari, I
Abstract : The increasing number of children with Costello syndrome described world wide has helped in delineating further the characteristic features of this condition. We report here two children, seen in the Genetic Division of the Brasilia University Hospital, showing the main features of the syndrome: "coarse" face, redundant skin on the feet and hands, hyperextensible hand and finger joints, curly hair, growth and psychomotor retardation, and feeding problems. In addition, one of the patients developed hydrocephalus during the evolution of the disease, making the third published patient with this complication. We discuss the appropriateness of serial brain imaging studies in Costello syndrome in light of the relative frequency of central nervous system malformations.